2014
DOI: 10.1007/s13277-014-1896-y
|View full text |Cite
|
Sign up to set email alerts
|

Common genetic variants on FOXE1 contributes to thyroid cancer susceptibility: evidence based on 16 studies

Abstract: Genome-wide association studies have identified polymorphisms at chromosome 9q22.23 as a new thyroid cancer (TC) susceptibility locus in populations of European descent. Since then, the relationship between three common variations (rs965513, rs1867277, and rs71369530) of FOXE1 and TC has been reported in various ethnic groups; however, the results have been inconclusive. To derive a more precise estimation of the relationship as well as to quantify the between-study heterogeneity and potential bias, a meta-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…LD between rs965513 and rs1867277 is significantly weaker in populations of African or Asian ancestry [20], which is not surprising, since the LD block structure may be different in individuals of different ancestry [22]. In our study we observed LD between rs965513, rs1867277, and rs1443434; however, that between rs1867277 and rs1443434 was the strongest.…”
Section: Prace Oryginalnesupporting
confidence: 52%
See 1 more Smart Citation
“…LD between rs965513 and rs1867277 is significantly weaker in populations of African or Asian ancestry [20], which is not surprising, since the LD block structure may be different in individuals of different ancestry [22]. In our study we observed LD between rs965513, rs1867277, and rs1443434; however, that between rs1867277 and rs1443434 was the strongest.…”
Section: Prace Oryginalnesupporting
confidence: 52%
“…lysed and confirmed in Caucasians [18][19][20], whereas rs944289 was associated with PTC in Asians, Europeans, and Americans [21] .…”
Section: Prace Oryginalnementioning
confidence: 81%
“…Kang J. et al included 8 studies corresponding to 2,085 cases and 10,341 controls [31]. Zhuang Y. et al included 13 studies involving 8491 cases, 103,218 control and 629 family members [32]. Ai L et al included 6 studies and a total of 52,363 individuals (5,193 cases vs. 47,170 controls) [33].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we evaluated the risk of thyroid cancer with rs965513 under several genetic models including the additive, recessive, dominant and homozygous models, to assess the increased levels of PTC risk under different genotypes. Zhuang et al evaluated the allelic, dominant and recessive models [32]. Ai L et al performed meta-analysis using additive model [33].…”
Section: Discussionmentioning
confidence: 99%
“…Besides medullary carcinoma, most of thyroid cancer originated in the follicular epithelial cells. The differentiated thyroid cancers (DTC) include papillary (PTC, 80-90% of cases) and follicular (FTC, 10% of cases) subtypes and their etiology are still not very clear [2]. It is no doubt that thyroid carcinoma is the result of interaction between genetic and environmental factors [3,4].…”
Section: Introductionmentioning
confidence: 99%